Are adverse childhood experiences scores associated with heroism or villainy? A quantitative observational study of Marvel and DC Cinematic Universe characters - Julia Wigmore; Bilal Ahmed; Gabriel Joaquino; Elke Jaibeeh Barah; Zahra Upal; Teressa Boring; Marika Lee; Eron Muel; Samantha Perry; Sandra Davidson; Carla Ginn; Carla Ferreira; et al. (PLoS ONE, 2025)
Many superhero and villain stories include trauma, which could influence how the public perceives the impact of trauma in their own lives. Our aim was to assess whether total Adverse Childhood Experiences (ACEs) scores were associated with heroism or villainy among Marvel and DC Characters. We watched 33 films, with a total runtime of 77 hours and 5 minutes. We scored 28 characters (19 men, 8 women, and 1 gender fluid). ACEs scores were evenly distributed across heroes/villains (U = 88, z = -.465, p = .642), Marvel/DC universes (U = 95.5, z = -0116, p = .907), and gender (U = 61, z = -.979, p = .328). There was no statistically significant correlation between ACEs scores and status (r(26) = .090, p = .65), universe (r(26) = .022, p = .91), or gender (r(26) = -.188, p = .34). We found that there was no association between ACEs scores and heroism or villainy. Thus, no one is doomed to be a villain just because of early childhood experiences.